The gender lie - Forrest, Bella (Forrest, Bella. Gender game, 2016)
After discovering the shocking secret buried deep within The Green, Violet has a grave decision to make. Trust the woman who saved her, or not? So far, everything about the woman has taken Violet by surprise. Her behavior has been honest and upfront, a refreshing change for Violet. Besides, with one of her loves ones hanging on life support, and the other close to falling completely out of reach, Violet doesn't exactly have a lot of choice. Her only way forward is to embark on a dicey excursion. For this, she knows she needs the Liberators' help, and must be prepared to take whatever risks that comes with. But what neither she, nor any of her new Liberator comrades can prepare for, is just how deep the lies of their homelands run.